e-Commerce dalam Manajemen Pemasaran - Surya Setyawan (Universitas Kristen Maranatha, 2003)
Nowadays development of telecommunication technologies set out to the development of internet. It can be said that everyone over the world use internet as communication media to communicate to everybody in every place in the world. Marketing management has to follow this development in satisfiying customers ' needs. Commercial business move from traditional commerce to e-commerce by usinginternet as world wide communication device. And so does marketing management change from local to global marketing. There are lots of changes in management skills and knowledges in marketing. This article describes the change of global world by understanding the internet; include its advantages and disadvantages. It will aflect to thedevelopment of e-commerce in marketing management. e.g. loyalty and value added.Keywords: Marketing management, internet. e-commerce, e-tailer, loyalty. value added. on-line.